2021
DOI: 10.1111/psyg.12668
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among physicians providing health care to the elderly in Japan: a qualitative study

Abstract: Background Physicians' job satisfaction plays an important role in service delivery. Japan is a country with a higher number of elderly people and their medical care is a crucial issue. To date, no study has been conducted on the job satisfaction of geriatricians serving the elderly in Japan. This study aims to explore the job satisfaction and motivation of physicians providing health care to the elderly working at different hospitals in Japan. Methods In‐depth interview of 23 geriatric physicians was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…As another example, this study suggested that such ethical decision-making tools were useful for ACP to help healthcare professionals as well as patients and families work through ethical complexities and ensure that both legal and ethical conflicts are addressed proficiently and to everyone's satisfaction. Although previous studies have dealt with job satisfaction among healthcare professionals providing end-of-life care [27][28][29][30], to the best of the authors' knowledge, few ethical tools highlight the satisfaction of end-of-life care teams with respect to ACP discussions.…”
Section: Discussionmentioning
confidence: 99%
“…As another example, this study suggested that such ethical decision-making tools were useful for ACP to help healthcare professionals as well as patients and families work through ethical complexities and ensure that both legal and ethical conflicts are addressed proficiently and to everyone's satisfaction. Although previous studies have dealt with job satisfaction among healthcare professionals providing end-of-life care [27][28][29][30], to the best of the authors' knowledge, few ethical tools highlight the satisfaction of end-of-life care teams with respect to ACP discussions.…”
Section: Discussionmentioning
confidence: 99%